Complete nucleotide sequence of an attenuated hepatitis A virus: comparison with wild-type virus. - Cohen, J I (1987)
The complete nucleotide sequence of an attenuated hepatitis A virus, HAV HM-175/7 MK-5, was determined from cloned cDNA. This virus was derived from wild-type HAV HM-175 after 32 passages in African green monkey kidney cells. The resultant cell culture-adapted virus is attenuated for chimpanzees. This virus was passaged an additional three times in monkey kidney cells to obtain sufficient virus for molecular cloning and was designated HM-175/7 MK-5. Three overlapping cDNA clones were obtained that together spanned the entire genome. Comparison of the nucleotide sequence of cDNA from wild-type virus (propagated in marmoset liver in vivo) with attenuated virus (grown in cell culture) showed 24 nucleotide changes distributed throughout the genome. Five base deletions occurred in the 5' noncoding region, and 12 of the 16 base substitutions in the coding region resulted in amino acid changes. Amino acid changes occurred in viral capsid proteins VP1 and VP2 and several of the nonstructural proteins. Thus, a small number of nucleotide changes are responsible for adaptation to cell culture and attenuation of HAV strain HM-175.